The future of food, land and water systems in the face of digital technologies - Veeger, Marieke; Jiménez, Daniel; Garcia Andarcia, Mariangel (International Water Management Institute, 2025)
The Future Scenarios Workshop on Digital Futures brought together experts from CGIAR centers and partners to explore how rapidly evolving digital technologies may reshape food, land, and water systems in the Global South. Using participatory foresight and human-centered design, participants identified signals and drivers of change—such as AI evolution, water governance, geopolitical tensions, and labor shifts—and combined them into scenario frameworks to guide the Digital Transformation Accelerator (DTA) and CGIAR’s broader digital strategy. The exercise produced three contrasting future worlds: Green India Revolution 2.0, where automation and AI transform agriculture but deepen social divides; We Are The Water, where transboundary water governance and decentralized cooperation redefine sovereignty; and Open Source, Open Borders, where migration and open digital ecosystems drive grassroots innovation and resilience. Cross-cutting insights reveal digital transformation’s potential to boost productivity, inclusion, and sustainability, while introducing risks of inequality, ethical data concerns, and greater energy and water dependence. These scenarios illustrate that digital change restructures power—who controls data, whose knowledge informs decisions, and whose interests prevail in FLW systems. CGIAR and partners are advised to invest in inclusive digital innovation, anticipate ethical risks, and strengthen cross-sectoral collaboration on technology and energy infrastructures to tackle challenges like water scarcity. The next phase will translate these insights into strategic action, embedding scenario thinking into CGIAR’s research, policy, and investment agendas for responsible digital transformation worldwide.